CONFIGURAÇÕES SUBJETIVAS NO DEBATE SOBRE MEIOS CONSENSUAIS DE RESOLUÇÃO DE CONFLITOS NA POLÍCIA RODOVIÁRIA FEDERAL - Martins, Claudio Edison Eusebio (2021)
This research addresses the topic of Consensual Conflict Resolution in the Public Service, as an alternative to regular disciplinary processing in the area of Administrative Disciplinary Law. Its application is through the Conduct Adjustment Term (TAC), which is an instrument aimed at solving conflicts in the organizational sphere. In this way, the subject emerges as the protagonist of a social space where diverse opinions and understandings coexist about the validity, usefulness and benefits for the server who agrees with the Administration through the TAC. Through subjectivity, it seeks a collective look that helps to understand the use of TAC in the view of the people involved in its application process. The research problem was to investigate challenges and difficulties in implementing TAC in the public service. The objective of the research was to understand subjective configurations in the debate on the implementation of consensual means of conflict resolution, as an alternative to the regular disciplinary processing in force in the Federal Highway Police (PRF), from the perspective of internal affairs officers in the State of Espírito Holy. The theoretical-methodological framework that supported this research was the Theory of Subjectivity in a Historical-Cultural Perspective, carried out from the principles of Qualitative Epistemology and the Constructive-interpretive Knowledge Method, whose research instrument was conversation. The main results found were the subjective configurations that point out the challenges and difficulties in implementing the TAC and the benefits arising from its application. Among the main ones are the possible legal weakness of the TAC rule and the weakening of the correctional system due to the implementation of this new mechanism. The institution has a history of combating serious functional irregularities, such as corruption, which generates achievements in the field of ethics and professionalism of public servants, which could be compromised with the advent of TAC, in the view of the research subjects. This can result from the lack of knowledge and distrust of the staff about the norm and the insufficient participation of the internal affairs area in the elaboration and implementation of this new mechanism, which is imposed by higher levels. On the other hand, there are visions that invest in new ways of confronting misconduct, based on prevention and professional training. The results also show an organization culturally divided, between adjectives of good and bad servants. A complex network of meanings and configurations emerges that involves debates about new ways of thinking and acting in relation to the consensual resolution of conflicts in the disciplinary field and seems to point to the future, as visions in the field of people's subjectivity begin to appear in the foreground, complementing functional or mechanical organizational views. The TAC brings achievements in the management field, such as reducing the number of Administrative Disciplinary Processes (PAD), improving Preliminary Summary Investigations (IPS) and repositioning servers in the correctional area. As suggestions for the evolution of the TAC, the need to review and improve the standard, in addition to the importance of emphasizing the educational aspect and preventive actions. The Technical Product produced was a Report to be delivered to the Inspector General of the Federal Highway Police (PRF), with a view to improving the use of TAC in the Institution.